Ocean oxygen: The role of the Ocean in the oxygen we breathe and the threat of deoxygenation - Grégoire, Marilaure; Oschlies, Andreas; Canfield, Donald; Castro, Carmen; Ciglenečki, Irena; Croot, Peter; Salin, Karine; Schneider, Birgit; Serret, Pablo; Slomp, Caroline; Tesi, Tommaso; Yücel, Mustafa (European Marine Board, 2023)
EMB Future Science Brief No. 10 highlights the most recent science on Ocean oxygen, including causes, impacts and mitigation strategies of Ocean oxygen loss, and discusses whether “every second breath we take comes from the Ocean”. It closes with key policy, management and research recommendations to address Ocean deoxygenation and communicate more accurately about the role of the Ocean in Earth’s oxygen. The sentence “every second breath you take comes from the Ocean” is commonly used in Ocean Literacy and science communication to highlight the importance of Ocean oxygen. However, despite its widespread use, it is often not phrased correctly. In contrast, there is little awareness about the threat of the global oxygen loss in the Ocean, called deoxygenation, particularly in comparison with other important stressors, such as Ocean acidification or increasing seawater temperatures. Deoxygenation is increasing in the coastal and open Ocean, primarily due to human-induced global warming and nutrient run-off from land, and projections show that the Ocean will continue losing oxygen as global warming continues. The consequences of oxygen loss in the Ocean are extensive and include decreased biodiversity, shifts in species distributions, displacement or reduction in fisheries resources, changes in biogeochemical cycling and mass mortalities. Low oxygen conditions also drive other chemical processes which produce greenhouse gases, toxic compounds and further degrade water quality. The degraded water quality directly affects marine ecosystems, but also indirectly impacts ecosystem services supporting local communities, regional economies and tourism. Although there are still gaps in our knowledge, we know enough to be very concerned about the consequences: the impacts might even be larger than from Ocean acidification or heat waves, and three out of the five global mass extinctions were linked to Ocean deoxygenation. The sense of urgency to improve Ocean health is reflected in the UN Decade of Ocean Science for ...